Solvent Isotopic Effects on a Surfactant Headgroup at the Air-Liquid Interface - Uvinduni I. Premadasa (2018)
© 2018 American Chemical Society. The geometry, arrangement, and orientation of a quaternary ammonium surfactant flanked by two methyl groups, a benzyl head, and an octyl tail were assessed at the air-water and air-deuterium oxide (D2O) interfaces using sum frequency generation vibrational spectroscopy. Remarkably, symmetric and asymmetric N-CH3stretches (at ∼2979 and ∼3045 cm-1, respectively, in the SSP polarization combination) were visible in water but negligible in deuterium oxide. We concluded that D2O addition triggers the average reorientation of the dimethyl amino units parallel to the interface and possibly changes the overall conformation of the surfactant. A reduced number of gauche defects in the surfactant octyl chain is also observed in D2O. Tilt angles for the octyl chain (1.0-10.8°) are consistent with an ordered monolayer at the air-liquid interface.